Green Growth Efficiency Evaluation of Major Domestic Oil-Gas Resource-Based Cities——Based on Panel Data of SBM Model and Malmquist-Luenberger Index - Shi, Hongjing; Li, Pengtai; Wei, Jingzhu; Shi, Songbai (Frontiers in Earth Science, 2022)
Based on the panel data of Jinzhou, Panjin, Songyuan, Daqing, Yangzhou, Dongying and other 20 oil and gas resource-based cities from 2010 to 2018, combined with DEA-SBM model and Malmquist-Luenberger index, using DEA-SOLVERPro 5.0 and MaxDEA software. This paper evaluates the green growth efficiency of oil and gas resource-based cities from static and dynamic perspectives.The results show that the average static efficiency of green growth of the main oil and gas resource-based cities in China does not reach 1, there is efficiency loss, and it does not reach Pareto optimum.The static efficiency of green growth of the eastern oil and gas resource-based cities is higher than that of other regions, which is in line with the law of the Environmental Kuznets Curve. The environment has been improved. More than half of the oil and gas resource-based cities have a dynamic efficiency value of green growth greater than 1, and the development trend of green growth is better.